2023
DOI: 10.3390/ma16155363
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Antibacterial, Fungicidal and Antiviral Properties of Selenium Nanoparticles

Dmitry A. Serov,
Venera V. Khabatova,
Vladimir Vodeneev
et al.

Abstract: The resistance of microorganisms to antimicrobial drugs is an important problem worldwide. To solve this problem, active searches for antimicrobial components, approaches and therapies are being carried out. Selenium nanoparticles have high potential for antimicrobial activity. The relevance of their application is indisputable, which can be noted due to the significant increase in publications on the topic over the past decade. This review of research publications aims to provide the reader with up-to-date in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 254 publications
(323 reference statements)
0
20
0
Order By: Relevance
“…The cell membrane broke down and lost its intrinsic function. TEM micrographs of SNP-treated E. coli cells showed that large gaps appeared in the cell membrane, and the bacteria were almost completely disintegrated into several parts [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell membrane broke down and lost its intrinsic function. TEM micrographs of SNP-treated E. coli cells showed that large gaps appeared in the cell membrane, and the bacteria were almost completely disintegrated into several parts [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, selenium nanoparticles (SeNPs) have emerged as promising candidates for a wide range of biomedical applications. 133–136 Their interesting and favourable in vitro and in vivo biological properties like low toxicity, biocompatibility, high bioavailability and degradability compared with organic and inorganic selenium compounds have made them suitable for several therapeutic applications such as anticancer, antibacterial, antifungal, anti-parasitic, antioxidant, anti-inflammatory and immune-stimulatory. 133–142 Of late their antiviral activities have also been explored.…”
Section: Antiviral Activity Of Selenium Nanoparticles (Senps)mentioning
confidence: 99%
“…This route being environmentally friendly is often referred to as the ‘green synthesis’ approach. There is a series of review articles dealing with the detailed methods of SeNP synthesis 133,135,136,144,147 and therefore not elaborated here.…”
Section: Antiviral Activity Of Selenium Nanoparticles (Senps)mentioning
confidence: 99%
“…NMs, with their trace elements, often show better physical and chemical properties than ordinary materials. Selenium (Se) is a trace element necessary for human metabolism, with a variety of health benefits such as antioxidant, antibacterial, cytoprotective, anti-inflammatory, and anti-cancer activities [ 16 , 17 ]. In addition, low concentrations of selenium have beneficial effects on plant growth, yield, and nutritional quality improvement.…”
Section: Introductionmentioning
confidence: 99%